(untitled) (VITAL, 2025)
The Faculty of Medicine is constantly renewing itself. The renovation of classrooms and University Wellness areas at the Circunvalar campus has been completed, including spaces for meditation and a gym. Block 1 was also renovated, featuring new offices, meeting rooms, and study areas. Additionally, a Primary Healthcare Ambulatory Center is planned for the Vívelo Mercurio Shopping Center in Soacha (Bogotá). This center will offer various low-cost services and provide opportunities for graduates, strengthening the accreditation process.